AN INTERNALIZATION OF THINK-PAIR-SHARE STRATEGY TO ELEVATE INDONESIAN EFL LEARNERS’ SPEAKING SKILLS - Wijaya, Kristian Florensio (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2025)
Mutual collaboration is considered amongst all notable ingredients to actualize more meaningful, interactive, and engaging EFL speaking learning dynamics. One of the main learner-oriented approaches fitting with this indispensable prerequisite is the think-pair-share strategy. It is believed by some researchers that under the constant enlightenment of the think-pair-share strategy, EFL learners are highly motivated to progress into various complex speaking learning activities as insistent mutual support from other learning counterparts is granted to them. Through this present small-scale library investigation, the researcher attempted to unravel the extent think-pair-share strategy promotes a particular set of benefits for improving Indonesian EFL learners’ communicative competencies. To that end, 30 prior mixed think-pair-share investigations were selected to generate more insightful research results. Taken from in-depth library analysis, two main research themes were yielded namely: (1) Think-pair-share strategy transforms EFL learners into more confident communicators and (2) EFL learners can expedite their speaking skills advancement through the use of think-pair-share strategy. Some recommendations for the betterment of this current qualitative study’s replication were depicted in an ultimate section.